2016
DOI: 10.1111/petr.12770
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes scores (SOFT,BAR, and Pedi‐SOFT) are accurate in predicting post‐liver transplant survival in adolescents

Abstract: SOFT and BAR scores utilize recipient, donor, and graft factors to predict the 3-month survival after LT in adults (≥18 years). Recently, Pedi-SOFT score was developed to predict 3-month survival after LT in young children (≤12 years). These scoring systems have not been studied in adolescent patients (13-17 years). We evaluated the accuracy of these scoring systems in predicting the 3-month post-LT survival in adolescents through a retrospective analysis of data from UNOS of patients aged 13-17 years who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This is in line with the findings of Schlegel et al who reported a related c-statistic of 0.754 for severe complications (CD≥3b) and 0.734 for 90-day mortality in case of the BAR-score [18]. The robust nature of the BAR score in predicting outcomes has been confirmed in other cohorts including pediatric/adolescent patients as well as in recipients of living donor liver transplantation [33, 34].…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with the findings of Schlegel et al who reported a related c-statistic of 0.754 for severe complications (CD≥3b) and 0.734 for 90-day mortality in case of the BAR-score [18]. The robust nature of the BAR score in predicting outcomes has been confirmed in other cohorts including pediatric/adolescent patients as well as in recipients of living donor liver transplantation [33, 34].…”
Section: Discussionsupporting
confidence: 86%
“…In one study, a c-index of 0.8 was reported for both the BAR and SOFT scores. 26 The D-MELD was also developed for patient survival. It has a relatively low reported predictive capacity, most likely because of its simplicity and because it is often applied to short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The BAR score fulfils all these criteria. Among risk scores which are based on data available at the time of organ acceptance, the BAR score performs best and its robustness in predicting post-transplant outcomes in various settings has been shown in multiple studies including ours [36][37][38].…”
Section: Discussionmentioning
confidence: 99%